The effect of thalidomide on vascular endothelial growth factor and tumor necrosis factor-? levels in retinal ischemia/reperfusion injury - Aydogan, Semih; Celiker, Uelkue; Tuerkcueoglu, Peykan; Ilhan, Nevin; Akpolat, Nusret (Springer, 2008)
Background To evaluate the effects of thalidomide treatment on the temporal course of TNF-alpha, VEGF production and the histopathological changes in ischemia/reperfusion (I/R) injured guinea pigs retina. Methods Control, ischemia, and thalidomide/ischemia groups including seven animals each were formed. Retinal ischemia was induced in male guinea pigs by cannulating anterior chambers and lifting the bottle to a height of 205 cm for 90 min in the ischemia and thalidomide/ischemia groups. The thalidomide/ischemia group received thalidomide (300 mg/kg/day) via nasogastric tube 24 h before ischemia and during 7 days of reperfusion. Guinea pigs were sacrificed for histopathological examination to evaluate the mean thickness of the inner plexiform layer (IPL), polymorphonuclear leukocyte (PMNL) infiltration, and biochemical analysis of retinal VEGF and TNF-alpha levels by ELISA. Results The mean retinal VEGF and TNF-alpha levels of the control, ischemia, and thalidomide/ischemia groups were 10.22 +/- 2.58 and 270.41 +/- 69.77 pg/ml; 35.80 +/- 5.97 and 629.93 +/- 146.41 pg/ml; 19.01 +/- 3.01 and 340.93 +/- 158.26 pg/ml, respectively. The retinal VEGF levels were significantly higher in I/R injured groups. The thalidomide/ischemia group retinal VEGF level was significantly lower versus the ischemia group. The retinal TNF-alpha levels were significantly elevated in the ischemia group, but no difference was observed between the thalidomide/ischemia and control groups. Also, the retinal TNF-alpha level was significantly lower in the thalidomide/ischemia group versus the ischemia group. The mean thickness of IPL and PMNL infiltration showed no difference between the control and thalidomide/ischemia groups. However, there was a significant difference between the control and ischemia groups. Conclusion Thalidomide treatment decreases PMNL infiltration, retinal edema, VEGF, and TNF-alpha synthesis following I/R injury to the guinea pig retina.
Keywords: thalidomide; retinal ischemia/reperfusion; VEGF; TNF-alpha